The Relationship Between Loneliness and Nomophobia Among Migrant Students in Banda Aceh - Rahmah, Sayidatur; Yasa, Rawdhah Binti; Zain, Fajran; Julianto, Rahmad (Fathana, 2024)
Loneliness is a feeling that arises due to a lack of interpersonal relationships and is considered unsatisfactory. One way to divert loneliness is to use a cell phone. Excessive use of cell phones can cause Nomophobia. This study aimed to determine the relationship between loneliness and Nomophobia in migrant students in Banda Aceh. This study uses a quantitative approach with the product-moment correlation method. This research uses the loneliness scale, developed based on aspects of loneliness identified by Peplau and Perlman (1981), with a reliability coefficient of 0.962. Additionally, it employs the nomophobia scale, based on aspects of Nomophobia identified by Yildirim and Coreia (2014), which has a reliability coefficient of 0.923. This study's population was migrant students active at the Ar-Raniry State Islamic University and Syiah Kuala University. The sampling technique used in this research is quota sampling with a total sample of 200 respondents. The study found a correlation coefficient of r = 0.209 with p = 0.002, indicating a significant positive relationship between loneliness and Nomophobia among migrant students in Banda Aceh. This means that the higher the loneliness, the higher the Nomophobia experienced by migrant students in Banda Aceh. Vice versa, the lower the loneliness, the lower the Nomophobia experienced by migrant students in Banda Aceh.